Broad‐Spectrum Antimicrobial Star Polycarbonates Functionalized with Mannose for Targeting Bacteria Residing inside Immune Cells. Issue 11 (29th March 2016) - Yang, Chuan; Krishnamurthy, Sangeetha; Liu, Jie; Liu, Shaoqiong; Lu, Xiaohua; Coady, Daniel J.; Cheng, Wei; De Libero, Gennaro; Singhal, Amit; Hedrick, James L.; Yang, Yi Yan
Abstract : In this study, a series of star‐shaped polycarbonates are synthesized by metal‐free organocatalytic ring‐opening polymerization of benzyl chloride (BnCl) and mannose‐functionalized cyclic carbonate monomers (MTC‐BnCl and MTC‐ipman) with heptakis‐(2, 3‐di‐O‐acetyl)‐β‐cyclodextrin (DA‐β‐CD) as macroinitiator. The distributions and compositions of pendent benzyl chloride and protected mannose group (ipman) units are facilely modulated by varying the polymerization sequence and feed ratio of the monomers, allowing precise control over the molecular composition, and the resulting polymers have narrow molecular weight distribution. After deprotection of ipman groups and quaternization with various N, N ‐dimethylalkylamines, these star polymers with optimized compositions of cationic and mannose groups in block and random forms exhibit strong bactericidal activity and low hemolysis. Furthermore, the optimal mannose‐functionalized polymer demonstrates mannose receptor‐mediated intracellular bactericidal activity against BCG mycobacteria without inducing cytotoxicity on mammalian cells at the effective dose. Taken together, the materials designed in this study have potential use as antimicrobial agents against diseases such as tuberculosis, which is caused by intracellular bacteria. Abstract : Antibacterial star polycarbonates containing mannose groups are synthesized. The mannose‐functionalized polymer of optimized composition demonstrates mannose receptor‐mediated intracellular activity against BCG mycobacteria without inducing cytotoxicity or hemolysis at the effective dose. It thus has potential as an antibacterial agent in treating infectious diseases caused by intracellular bacteria such as tuberculosis.